First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Correction to: The thyroid status reprograms T cell lymphoma growth and modulates immune cell frequencies - H. A. Sterle; M. L. Barreiro Arcos; E. Valli; M. A. Paulazo; S. P. Méndez Huergo; A. G. Blidner; F. Cayrol; M. C. Díaz Flaqué; A. J. Klecha; V. A. Medina; L. Colombo; G. A. Rabinovich; et al. (Journal of Molecular Medicine, 2023)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Projected declines in global DHA availability for human consumption as a result of global warming - Stefanie M. Colombo; Timothy F. M. Rodgers; Miriam L. Diamond; Richard P. Bazinet; Michael T. Arts (Ambio, 2020)
Docosahexaenoic acid (DHA) is an essential, omega-3, long-chain polyunsaturated fatty acid that is a key component of cell membranes and plays a vital role in vertebrate brain function. The capacity to synthesize DHA is limited in mammals, despite its critical role in neurological development and health. For humans, DHA is most commonly obtained by eating fish. Global warming is predicted to reduce the de novo synthesis of DHA by algae, at the base of aquatic food chains, and which is expected to reduce DHA transferred to fish. We estimated the global quantity of DHA (total and per capita) currently available from commercial (wild caught and aquaculture) and recreational fisheries. The potential decrease in the amount of DHA available from fish for human consumption was modeled using the predicted effect of established global warming scenarios on algal DHA production and ensuing transfer to fish. We conclude that an increase in water temperature could result, depending on the climate scenario and location, in a ~ 10 to 58% loss of globally available DHA by 2100, potentially limiting the availability of this critical nutrient to humans. Inland waters show the greatest potential for climate-warming-induced decreases in DHA available for human consumption. The projected decrease in DHA availability as a result of global warming would disproportionately affect vulnerable populations (e.g., fetuses, infants), especially in inland Africa (due to low reported per capita DHA availability). We estimated, in the worst-case scenario, that DHA availability could decline to levels where 96% of the global population may not have access to sufficient DHA.

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Beneficial and Safety Properties of a Corynebacterium vitaeruminis Strain Isolated from the Cow Rumen - M. Colombo; N. P. A. Castilho; S. D. Todorov; L. A. Nero (Probiotics and Antimicrobial Proteins, 2017)

Effects of aerobic exercise training on metabolism of nitric oxide and endothelin-1 in lung parenchyma of rats with pulmonary arterial hypertension - A. Zimmer; R. B. Teixeira; J. H. P. Bonetto; R. Siqueira; C. C. Carraro; L. M. Donatti; A. Hickmann; I. E. Litvin; A. E. G. Godoy; A. S. Araujo; R. Colombo; Adriane Belló-Klein (Molecular and Cellular Biochemistry, 2017)

Paediatric nasopharyngeal cytology: a new diagnostic opportunity? - S. Torretta; P. Marchisio; M. R. Colombo; C. Rosazza; L. Pignataro (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

The thyroid status reprograms T cell lymphoma growth and modulates immune cell frequencies - H. A. Sterle; M. L. Barreiro Arcos; E. Valli; M. A. Paulazo; S. P. Méndez Huergo; A. G. Blidner; F. Cayrol; M. C. Díaz Flaqué; A. J. Klecha; V. A. Medina; L. Colombo; G. A. Rabinovich; et al. (Journal of Molecular Medicine, 2016)

Is the recent decrease in airborne Ambrosia pollen in the Milan area due to the accidental introduction of the ragweed leaf beetle Ophraella communa? - M. Bonini; B. Šikoparija; M. Prentović; G. Cislaghi; P. Colombo; C. Testoni; L. Grewling; S. T. E. Lommen; H. Müller-Schärer; M. Smith (Aerobiologia, 2015)

Sun‐induced fluorescence – a new probe of photosynthesis: First maps from the imaging spectrometer HyPlant - U. Rascher; L. Alonso; A. Burkart; C. Cilia; S. Cogliati; R. Colombo; A. Damm; M. Drusch; L. Guanter; J. Hanus; T. Hyvärinen; T. Julitta; et al. (Global Change Biology, 2015)
Variations in photosynthesis still cause substantial uncertainties in predicting photosynthetic CO 2 uptake rates and monitoring plant stress. Changes in actual photosynthesis that are not related to greenness of vegetation are difficult to measure by reflectance based optical remote sensing techniques. Several activities are underway to evaluate the sun‐induced fluorescence signal on the ground and on a coarse spatial scale using space‐borne imaging spectrometers. Intermediate‐scale observations using airborne‐based imaging spectroscopy, which are critical to bridge the existing gap between small‐scale field studies and global observations, are still insufficient. Here we present the first validated maps of sun‐induced fluorescence in that critical, intermediate spatial resolution, employing the novel airborne imaging spectrometer HyPlant . HyPlant has an unprecedented spectral resolution, which allows for the first time quantifying sun‐induced fluorescence fluxes in physical units according to the Fraunhofer Line Depth Principle that exploits solar and atmospheric absorption bands. Maps of sun‐induced fluorescence show a large spatial variability between different vegetation types, which complement classical remote sensing approaches. Different crop types largely differ in emitting fluorescence that additionally changes within the seasonal cycle and thus may be related to the seasonal activation and deactivation of the photosynthetic machinery. We argue that sun‐induced fluorescence emission is related to two processes: (i) the total absorbed radiation by photosynthetically active chlorophyll; and (ii) the functional status of actual photosynthesis and vegetation stress.

Direct numerical simulation of fully saturated flow in natural porous media at the pore scale: a comparison of three computational systems - M. Siena; J. D. Hyman; M. Riva; A. Guadagnini; C. L. Winter; P. K. Smolarkiewicz; P. Gouze; S. Sadhukhan; F. Inzoli; G. Guédon; E. Colombo (Computational Geosciences, 2015)

Combined effects of arbuscular mycorrhizal fungi and exogenous cytokinins on pomegranate (Punica granatum) under two contrasting water availability conditions - M. J. Bompadre; L. Fernández Bidondo; V. A. Silvani; R. P. Colombo; M. Pérgola; A. G. Pardo; A. M. Godeas (Symbiosis, 2015)

B25716/1: a novel albumin-binding Gd-AAZTA MRI contrast agent with improved properties in tumor imaging - E. Gianolio; C. Cabella; S. Colombo Serra; G. Valbusa; F. Arena; A. Maiocchi; L. Miragoli; F. Tedoldi; F. Uggeri; M. Visigalli; P. Bardini; S. Aime (JBIC Journal of Biological Inorganic Chemistry, 2014)

Differential efficiency of two strains of the arbuscular mycorrhizal fungus Rhizophagus irregularis on olive (Olea europaea) plants under two water regimes - M. J. Bompadre; M. C. Rios De Molina; R. P. Colombo; L. Fernandez Bidondo; V. A. Silvani; A. G. Pardo; J. A. Ocampo; A. M. Godeas (Symbiosis, 2013)

Effect of Early Introduction of Microencapsulated Diet to Larval Atlantic Halibut, Hippoglossus hippoglossus L. Assessed by Microarray Analysis - H. M. Murray; S. P. Lall; R. Rajaselvam; L. A. Boutilier; R. M. Flight; B. Blanchard; S. Colombo; V. Mohindra; M. Yúfera; S. E. Douglas (Marine Biotechnology, 2010)

Global Distribution and Outcomes for Candida Species Causing Invasive Candidiasis: Results from an International Randomized Double-Blind Study of Caspofungin Versus Amphotericin B for the Treatment of Invasive Candidiasis - A. L. Colombo; J. Perfect; M. DiNubile; K. Bartizal; M. Motyl; P. Hicks; R. Lupinacci; C. Sable; N. Kartsonis (European Journal of Clinical Microbiology & Infectious Diseases, 2003)

Immunolocalization of the petunia floral binding proteins 7 and 11 during seed development in wild-type and expression mutants ofPetunia hybrida - P. E. Wittich; R. F. de Heer; X. -F. Cheng; H. Kieft; L. Colombo; G. C. Angenent; A. A. M. van Lammeren (Protoplasma, 1999)